2005
DOI: 10.1002/cm.20100
|View full text |Cite
|
Sign up to set email alerts
|

CLAMP, a novel microtubule‐associated protein with EB‐type calponin homology

Abstract: In the Addendum on page 154 and in the article's reference section, the reference [Chan et al., 2005] was omitted. The sentence in the Addendum should have read: After submission of this manuscript, a report [Chan et al., 2005] described a gene sequence named Spef1 that is identical to CLAMP and is localized to mouse sperm flagella.The full reference for [Chan et al., 2005]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Contrary to studies of Xenopus epidermal cells, which are facilitated by the availability of markers used in immunofluorescence (26)(27)(28), mammalian cilia polarity is usually investigated by transmission EM (4,6,7,29,30), which is hardly compatible with tissue-wide polarity analysis. To circumvent this difficulty, we tested a variety of markers and found that phospho-β-catenin (P-βCat) (31)(32)(33), Chibby (29), FGFR1 Oncogene Partner (34), and Clamp (26,35) localized at the base of cilia, and when combined with γ-tubulin immunostaining, they clearly delineate cilia polarity. The P-βCat signal was adjacent to that of γ-tubulin; at the side opposite to the basal foot, a lateral extension of BBs pointing in the direction of the cilia beats effective stroke (Fig.…”
Section: Significancementioning
confidence: 99%
“…Contrary to studies of Xenopus epidermal cells, which are facilitated by the availability of markers used in immunofluorescence (26)(27)(28), mammalian cilia polarity is usually investigated by transmission EM (4,6,7,29,30), which is hardly compatible with tissue-wide polarity analysis. To circumvent this difficulty, we tested a variety of markers and found that phospho-β-catenin (P-βCat) (31)(32)(33), Chibby (29), FGFR1 Oncogene Partner (34), and Clamp (26,35) localized at the base of cilia, and when combined with γ-tubulin immunostaining, they clearly delineate cilia polarity. The P-βCat signal was adjacent to that of γ-tubulin; at the side opposite to the basal foot, a lateral extension of BBs pointing in the direction of the cilia beats effective stroke (Fig.…”
Section: Significancementioning
confidence: 99%
“…One head contains Nuf2 and Ndc80, which each contain positively charged calponinhomology domains (CH) that facilitate binding to the negative microtubule surface (Wei et al 2005;Cheeseman et al 2006;Wei et al 2007;Ciferri et al 2008). CH domains have diverse functions and have been identified in other microtubule binding proteins (Hayashi and Ikura 2003;Dougherty et al 2005). An unstructured N-terminal tail on Ndc80 enhances the microtubule binding activity of the complex (Wei et al 2005;DeLuca et al 2006;Wei et al 2007;Ciferri et al 2008;Miller et al 2008;Alushin et al 2010), although it is not essential for yeast viability due to redundancy with Dam1 (Kemmler et al 2009;Demirel et al 2012;Lampert et al 2013).…”
Section: Kmnmentioning
confidence: 99%
“…Spef1/CLAMP interacts with microtubules through a calponin homology domain and thus promotes microtubule bundling and microtubule stabilization (35). In T. brucei, a single Spef1 homolog (also known as TbCMF18) is present.…”
Section: Identification Of Bi-lobe-associated Proteins By Lc/ms-ms-mentioning
confidence: 99%